ANALISIS KESULITAN SISWA SMP DALAM MENYELESAIKAN SOAL CERITA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL MELALUI PEMBELAJARAN DARING - Neng Wiwit Juwita Lestari; M. Afrilianto (IKIP Siliwangi, 2021)
Mathematics is a skill that must be possessed by everyone because it is applied in almost every aspect of life. This study aims to observe the difficulties of junior high school students in solving the Two Variable Linear Equation System (SPLDV) material using online learning. For the 2020-2021 academic year, this research was conducted at one of the Cianjur State Junior High Schools. The subjects were 20 students from class IX. This study has test questions with indicators that have been set as instruments. A qualitative descriptive approach was used in this study. The findings obtained, some students have difficulty with indicators to solve problems involving a two-variable linear equation system (SPLDV). The results of the analysis show that (1) Lack of mastery of story problems; (2) Obstacles in converting story problems into mathematical models; (3) Do not understand the concept so that students need to be explored or trained more deeply.